ECG interpretation made incredibly easy!. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"ECG Interpretation Made Incredibly Easy, Fifth Edition makes learning to read and interpret rhythm strips easy and fun. This practical and entertaining reference uses a unique, light-hearted writing style that makes learning this complex information non-threatening and highly enjoyable. The book reviews fundamental cardiac anatomy and physiology, explains how to obtain and interpret a rhythm strip, and teaches the reader how to recognize and treat sinus, atrial, and ventricular arrhythmias as well as heart blocks. In addition, the book explains how to obtain and interpret 12-lead ECGs. Special elements found throughout the reference make it easy to remember key points. Each chapter features: A summary of key points; clear, simple explanations of problems; definitions of key terms; illustrations that clearly explain key concepts; bullets, ballot boxes, and checklists that make it easy to spot important points at a glance; sidebars that highlights key facts about ECG interpretation; quick quizzes to test knowledge"--Provided by publisher.